(untitled) (The Research of Medical Science Review, 2024)
This study explored the influence of superstitious beliefs on patients' attitudes towards seeking assistance and their perceptions of mental illness in Pakistan. In this context, supernatural theories often intertwine with religious and cultural frameworks, shaping public attitudes towards mental health issues. The research employed detailed interviews and thematic analysis to examine how these beliefs contribute to stigma and disgrace, misconceptions and misunderstanding, and delays in accessing professional mental health care. Findings revealed that individuals with mental health conditions frequently attribute their symptoms to black magic or supernatural forces, leading them and their families to prefer traditional or religious remedies over professional mental health treatment. The study accentuated the complex interplay between modern psychological concepts and traditional superstitions. it emphasizing the need for culturally sensitive approaches to enhance mental health awareness and improve access to quality care in Pakistan. It highlighted the importance of collaboration among mental health professionals, religious leaders, and community members to address these challenges and promote better understanding and treatment of mental illness within the context of prevailing superstitions.